Fatigue Performance of the Novel Titanium Alloy Timetal 407 - Martin Bache (MATEC Web of Conferences, 2018)
Timetal 407 (Ti-407) is a novel titanium alloy formulated as a lower strength, more malleable alloy offering a range of cost reduction opportunities compared with Ti-6-4 (Ti-6Al-4V). An investigation of the room temperature, high cycle and low cycle fatigue properties of Ti-407 is presented. The effect of thermo-mechanical processing on microstructure is characterised and the fatigue properties of a microstructure containing 30-40% primary alpha volume fraction are presented and discussed. The Ti-407 results are compared with data generated from Ti-6-4 processed to provide a similar microstructure, to demonstrate both superior HCF endurance strength and ductility of the former.